PERLINDUNGAN HUKUM BAGI NASABAH DALAM PENGGUNAAN SISTEM APLIKASI PERBANKAN BERBASIS MOBILE APPLICATION (ANDROID DAN IOS) YANG DIGUNAKAN UNTUK MELAKUKAN TRANSAKSI PERBANKAN (STUDI PADA BANK PEMBANGUNAN DAERAH LAMPUNG) - Lukmanul Hakim; Aprinisa Aprinisa; Kelvin Ardy Irawan (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
The presence of e-banking has now provided simplicity in transactions for customers, this is one form of bank motivation towards technological developments. Today's modern customers coexist with a variety of technological conveniences, simultaneously coexisting with risks that can occur at any time. Risks must be in line with legal certainty regarding the use of the rights of all Indonesian citizens which must be upheld and fought for in order to implement Article 28D of the 1945 Constitution. Therefore, this study aims to analyze regulatory protection arrangements for bank customers in conducting e-banking service transactions and to discuss the responsibility of the bank's rules for customers who are disadvantaged in conducting e-banking service transactions. This research uses a normative method using a statutory & conceptual approach. Sources of research rules consist of primary, secondary and tertiary sources using recording and documenting techniques as data collection techniques. The results of this study describe that bank customers carrying out e-banking transactions have not been supported by a special regulation, permanent customers are given preventive as well as repressive protection. The responsibility of the bank's rules for customers who lose in e-banking transactions will be compensated if the customer is able to show that it is true that the loss occurred as a result of the bank's mistake. Complaints to the bank both verbally and in writing can be carried out by customers. Concurrency settlement can be done through litigation, non-litigation or LAPS in the financial services sector.